An informed community's perception of the impact of digital technology on the credibility of news photography - LÃ zaro, Angelique Maria (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2000)
South African photojournalists' perception of digital technology's impact on the credibility of news photographs is investigated in this study. Digital technology has the capabilities to produce "manipulated" photographs that appear realistic and credible. Credibility is dependent on a variety of factors including codes of realism and codes of production, which fit conventional codes of photographic representation. Manipulation is the act of deviating from accepted codes of photographic representation that may jeopardise the credibility of news photography. This thesis proposes a new theoretical framework that encompasses existing theories of semiotics, ideology, naturalism, realism and credibility. These theories underpin the definitions and discussion on manipulation and credibility. A descriptive survey is used which attempts to discover photojournalists' views towards credibility. This research draws on qualitative research methods using a largely qualitative questionnaire, which generates both qualitative and quantitative data. The questions are formulated around two case studies of digitally manipulated photographs. The trends and responses in the research data are connected and discussed. The findings of this study are discussed in terms of credibility, awareness of the digital changes, the reason for the changes, the role of a caption, deletion techniques and background changes. The empirical situation is analysed in relation to the theoretical discussions and this study's theorisation of photographic representation.
Keywords: Photojournalism -- Moral and ethical aspects; Digital media; Photojournalists; Photography -- Digital techniques